Access to Interaction and Context Through Situated Descriptions: A Study of Interpreting for Deafblind Persons - Raanes, Eli (Frontiers in Psychology, 2020)
This article focuses on how to provide environmental descriptions of the context with the intent of creating access to information and dialogical participation for deafblind persons. Multimodal interaction is needed to communicate with deafblind persons whose combined sensory loss impedes their access to the environment and ongoing interaction. Empirical data of interpreting for deafblind persons are analyzed in order to give insight into how this task may be performed. All communicative activities vary due to their context, participants, and aim. In this study our data, part of a cross-linguistic study of tactile sign language, were gathered during a guided tour for a deafblind group. The guided tour was tailored to a specific group (adult deafblind tactile signers and their interpreters) visiting one of the oldest cathedrals and pilgrim sites in Scandinavia, with interpreters following up the guide’s presentation and providing descriptions based on the given situation. The tour and the interpreters’ work was videotaped, and the ongoing interaction and communication has been studied through video-ethnographic methods and conversational analysis. Theories from multimodality communicative studies are relevant for the ways tactile descriptions are presented and analyzed. Some of this is an investigation at a micro-level of interaction. An overall inspiration for this study is interaction studies with data from authentic formal and informal conversations and ways of analyzing embodied action and situated gestures in studies of human interaction. Also, concepts of “frontstage,” “backstage,” and “main conversation” are brought into our interpreter-mediated data in order to follow the role of building meaning in complex conversations. Theories on interaction are used in our analyses to illustrate the participating framework between the guide, interpreter, the deafblind person and the situated frame of their interaction. The study opens for a broader understanding of the repertoire of multimodal interaction and how such interaction may be handled as inputs in communication processes. This is of relevance for communication with deafblind persons and for knowledge of multimodal interaction in general.